PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR SISWA IPAS KELAS IV DI SD NEGERI 071218 FONDAKORAYA KABUPATEN NIAS SELATAN - Mitra Wati Ndruru; Bogor Lumbanraja; Eka Margareta Sinaga; Regina Sipayung; Juliana; Patri Janson Silaban (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine the influence of the Problem Based Learning model on the science learning outcomes of fourth-grade students at SD Negeri 071218 Fondakoraya, South Nias Regency, for the 2024/2025 academic year. This research employed a quantitative research method and a pre-experimental research design. The population of this research was all fourth-grade students at SD Negeri 071218 Fondakoraya. The sample was selected using saturated sampling, where all 30 fourth-grade students at SD Negeri 071218 Fondakoraya were included as the sample. To ascertain the students' initial abilities, the researcher conducted a pre-test with an average score of 45.56, which falls into the "needs guidance" category. Following the implementation of the Problem Based Learning model, the students' learning outcomes showed an improvement in the post-test, with an average score of 82.93, categorized as "good." The increase in the level of success of students' learning outcomes was evidenced by the correlation test result, which yielded a value of 0.975, indicating a very strong correlation, meaning that rcount​ (0.975) ≥ rtable​ (0.361). Furthermore, the hypothesis testing (t-test) showed that tcount​ ≥ ttable​, specifically 23.442 ≥ 1.697, thus indicating that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. This demonstrates that there is an influence of the Problem Based Learning model on the science learning outcomes of fourth-grade students at SD Negeri 071218 Fondakoraya.